Respuesta :

Answer:

{x = 1, y = -5

Step-by-step explanation:

Solve the following system:

{-3 x - 3 y = 12 | (equation 1)

{3 y - 9 x = -24 | (equation 2)

Swap equation 1 with equation 2:

{-(9 x) + 3 y = -24 | (equation 1)

{-(3 x) - 3 y = 12 | (equation 2)

Subtract 1/3 × (equation 1) from equation 2:

{-(9 x) + 3 y = -24 | (equation 1)

0 x - 4 y = 20 | (equation 2)

Divide equation 1 by 3:

{-(3 x) + y = -8 | (equation 1)

{0 x - 4 y = 20 | (equation 2)

Divide equation 2 by 4:

{-(3 x) + y = -8 | (equation 1)

{0 x - y = 5 | (equation 2)

Multiply equation 2 by -1:

{-(3 x) + y = -8 | (equation 1)

{0 x+y = -5 | (equation 2)

Subtract equation 2 from equation 1:

{-(3 x)+0 y = -3 | (equation 1)

{0 x+y = -5 | (equation 2)

Divide equation 1 by -3:

{x+0 y = 1 | (equation 1)

{0 x+y = -5 | (equation 2)

Collect results:

Answer:  {x = 1 , y = -5

ACCESS MORE